Analisis Profitabilitas Melalui Likuiditas, Kualitas Aset, Solvabilitas - Cahyanti, Ni Komang Yunita; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
Bank is defined as an institution with the function of collecting public funds in the form of savings and then channeling them to the public in the form of credit or other forms with the hope of increasing living standards. This research focuses on analyzing the relationship between liquidity, asset quality, solvency and profitability through multiple linear regression. The research sample is 45 banking companies listed on the Indonesia Stock Exchange using purposive sampling method. Unrelated Loan to Deposit Ratio and Debt to Asset Ratio were found with Return On Assets, while Non Performing Loans had a significant negative association with Return On Assets in the companies studied. Keywords: Loan to Deposit Ratio; Non Performing Loan; Debt to Asset Ratio; Return On Asset